Design of a Basic Chemistry Textbook for Biology Education Incorporating Science, Environment, Technology, and Society (SETS) and Integrating Islamic Values - Hayati, Dwi Kurnia; Hakim, Nasrul; Anggraini, Septika (Universitas Khairun, 2025)
Teaching materials are one of the essential tools for achieving quality learning. A needs analysis revealed the absence of a basic chemistry textbook tailored for biology education. This research aims to develop a basic chemistry textbook for biology education that incorporates SETS (Science, Environment, Technology, and Society) and integrates Islamic values. It also aims to analyze its feasibility and practicality. The research method employed the 4D development model, which consists of Define, Design, Develop, and Disseminate. The final product validation results showed a score percentage of 90.28% for material validation, 91.67% for design validation, and 92.5% for the integration of Islamic values validation. Overall, the validation results categorized the textbook as highly feasible for use. The practicality test, conducted through questionnaires distributed to students who used the product, yielded a score percentage of 85.67%, which falls into the